2009
DOI: 10.1002/ejic.200900347
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis, Structure, and FTIR Spectroelectrochemistry of W(CO)5 Complexes of 4‐Oxo‐4‐(2,5‐dimethylazaferrocen‐1′‐yl)butanoic and 5‐Oxo‐5‐(2,5‐dimethylazaferrocen‐1′‐yl)pentanoic Acids

Abstract: With the aim of developing new IR-detectable metal-carbonyl tracers for the amino function, we have synthesized W(CO) 5 complexes of 4-oxo-4-(2,5-dimethylazaferrocen-1Ј-yl)butanoic acid (2) and 5-oxo-5-(2,5-dimethylazaferrocen-1Ј-yl)pentanoic acid (3) by AlCl 3 -catalyzed Friedel-Crafts reaction of W(CO) 5 -2,5-dimethylazaferrocene (1) with succinic or glutaric anhydride. Complexes 2 and 3 are thermally stable and display sharp, intense absorption bands of tungsten-coordinated CO ligands at ca. 1923 cm -1 . In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…This (11) 1.473 (5) 1.468(6) C(11)eC (12) 1.516 (5) 1.491(6) C(11)eO (1) 1.223(4) 1.221(5) C(12)eC (13) 1.500 (5) 1.309(7) C(13)eC(l1) 1.781(4) e C(2)eN(1)eC (5) 106.5(3) 106.1(3) W(1)eN(1)eC (2) 68.8(2) 68.9(2) W(1)eN(1)eC (5) 69.5(2) 69.4(2) O(1)eC(11)eC (10) 121.0(3) 120.4(4) O(1)eC(11)eC (12) 121.6(3) 120.7(4) C(10)eC(11)eC (12) 117.3 (3) 118.9(4) C(11)eC(12)eC (13) 114.6(3) 122.6(4) C(11)eC(13)eC (12) 112.8(3) e C(10)eC(11)eC(12)eC (13) 173.9(5) 179.8(4) O(1)eC(11)eC(12)eC (13) À5.4(5) À0.4 (7) reflects a weak but still measurable electron-withdrawing effect of the thymine end-chain group. The observed voltammetric profiles of W(CO) 5 -2,5-dimethylazaferrocenes 12a and 12b closely resemble ones reported by us previously for other W(CO) 5 -2,5-dimethylazaferrocenes derivatives [50]. In anodic scans, cyclic voltammograms of 12a and 12b shows two waves.…”
Section: Cyclic Voltammetrical Study Of 11c 11d 12a and 12bsupporting
confidence: 85%
See 1 more Smart Citation
“…This (11) 1.473 (5) 1.468(6) C(11)eC (12) 1.516 (5) 1.491(6) C(11)eO (1) 1.223(4) 1.221(5) C(12)eC (13) 1.500 (5) 1.309(7) C(13)eC(l1) 1.781(4) e C(2)eN(1)eC (5) 106.5(3) 106.1(3) W(1)eN(1)eC (2) 68.8(2) 68.9(2) W(1)eN(1)eC (5) 69.5(2) 69.4(2) O(1)eC(11)eC (10) 121.0(3) 120.4(4) O(1)eC(11)eC (12) 121.6(3) 120.7(4) C(10)eC(11)eC (12) 117.3 (3) 118.9(4) C(11)eC(12)eC (13) 114.6(3) 122.6(4) C(11)eC(13)eC (12) 112.8(3) e C(10)eC(11)eC(12)eC (13) 173.9(5) 179.8(4) O(1)eC(11)eC(12)eC (13) À5.4(5) À0.4 (7) reflects a weak but still measurable electron-withdrawing effect of the thymine end-chain group. The observed voltammetric profiles of W(CO) 5 -2,5-dimethylazaferrocenes 12a and 12b closely resemble ones reported by us previously for other W(CO) 5 -2,5-dimethylazaferrocenes derivatives [50]. In anodic scans, cyclic voltammograms of 12a and 12b shows two waves.…”
Section: Cyclic Voltammetrical Study Of 11c 11d 12a and 12bsupporting
confidence: 85%
“…Pertinent data are collected in Table 4 along with electrochemical data for known W(CO) 5 -2,5-dimethylazaferrocene 12 [50], 3-chloropropionylferrocene 11a and acryloylferrocene 11b as a comparison. Figs.…”
Section: Cyclic Voltammetrical Study Of 11c 11d 12a and 12bmentioning
confidence: 99%
“…It can be seen that there is considerable variation in the positions of the symmetric and antisymmetric bands. The expectation is that binding a metal cation in the crown influences charge distribution in the complex in much the same way as has been observed11 for hydrogen bonding at pyrazine ligands in Cr(CO) 5 complexes, for dissociation of carboxylic acid substituents on ligands in Fe(CO) 3 and Cr(CO) 3 complexes,12 and in an electrochemical investigation13 of W(CO) 5 (azaferrocene) adducts with potential applications as IR‐detectable tracers for amino groups. In previous studies14 we have found that Bellamy plots15 are a convenient method to depict results of this type.…”
Section: Resultsmentioning
confidence: 65%